2014
DOI: 10.1016/j.exer.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding photoreceptor outer segment phagocytosis: Use and utility of RPE cells in culture

Abstract: RPE cells are the most actively phagocytic cells in the human body. In the eye, RPE cells face rod and cone photoreceptor outer segments at all times but contribute to shedding and clearance phagocytosis of distal outer segment tips only once a day. Analysis of RPE phagocytosis in situ has succeeded in identifying key players of the RPE phagocytic mechanism. Phagocytic processes comprise three distinct phases, recognition/binding, internalization, and digestion, each of which is regulated separately by phagocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(189 citation statements)
references
References 86 publications
(152 reference statements)
5
172
3
Order By: Relevance
“…Lastly, we showed that most (if not all) of the phagocytosis observed was mediated through the aVb5 receptor, which is a key player involved in the initial specific recognition of ROS in RPE cells. 34,35 Additional studies are needed to determine whether primary RPE or RPE derived from either human embryonic stem cells or induced pluripotent stem cells (iPSC) would behave similarly on spontaneously aged or nitrite-modified ECM surfaces. Ongoing experiments in our laboratory are aimed at understanding the effects of BM-aging on iPSC-derived RPE cells derived from AMD patients and unaffected controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we showed that most (if not all) of the phagocytosis observed was mediated through the aVb5 receptor, which is a key player involved in the initial specific recognition of ROS in RPE cells. 34,35 Additional studies are needed to determine whether primary RPE or RPE derived from either human embryonic stem cells or induced pluripotent stem cells (iPSC) would behave similarly on spontaneously aged or nitrite-modified ECM surfaces. Ongoing experiments in our laboratory are aimed at understanding the effects of BM-aging on iPSC-derived RPE cells derived from AMD patients and unaffected controls.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, approximately 3% to 5% of the distal tips of photoreceptor outer segments are shed on a daily basis and proper RPE phagocytosis is necessary to maintain the health and integrity of the neural retina and the choriocapillaris. 33,34 RPE phagocytosis uses aVb5 integrin receptors on the RPE surface for initial outer segment cell surface binding, the receptor MerTK for internalization, and the scavenger receptor CD36. 31,35,36 Disruption of any step in this process can lead to pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptors (PRs) and the retinal pigment epithelium (RPE) are commonly considered the most important targets of stem cell therapies [1][2][3]. PRs and RPE interact functionally and structurally [2][3][4][5][6], appear to polarize each other [7], and are reported to show improved engraftment when transplanted together [8,9]. After engraftment, stem cell-derived PRs must survive and form functional synaptic connections.…”
mentioning
confidence: 99%
“…The different phases of uptake can also distinguished in vitro by using appropriate experimental procedures 39 . Pulse-chase experiments can be performed using temperature switch: POS binding occurs at 20 °C while internalization needs a temperature of 37 °C to proceed 32,40,7 .…”
Section: Representative Resultsmentioning
confidence: 99%